Integrating Higher-Order Thinking Skills in Mathematics Education: Development of Learning Tools for Patterns and Number Sequences - Ega Gradini; Edy Saputra; Novita Rahmayanti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
Integrating Higher-Order Thinking Skills in Mathematics Education: Development of Learning Tools for Patterns and Number Sequences.Â Employing the 4-D development model (Define, Design, Develop, Disseminate), this study aimed to develop and validate Higher Order Thinking Skills (HOTS)-based learning tools for number sequence patterns. The define stage identified needs and specifications, while the design stage focused on lesson plans, teacher manuals, student books, and worksheets. Developed tools underwent limited trials in a grade VIII class. The initial lesson plans required revision due to a low RVI (0.70), but after revision, achieved a satisfactory RVI (0.85). The teacher's manual demonstrated high validity (RVI = 0.871), indicating its readiness for instruction. Similarly, the student book required revision due to a low initial RVI (0.63) but achieved validity (RVI = 0.77) after revision. Worksheets also exhibited high validity (RVI = 0.80). All developed components (lesson plans, teacher manuals, student books, and worksheets) achieved RVI values above 0.75, signifying that these HOTS-oriented mathematics learning tools meet quality standards and are ready for use in HOTS-oriented mathematics instruction. This implementation is expected to enhance teaching and learning effectiveness, ultimately leading to optimal learning outcomes.